Adaptations to Climate Variability in Northern Uganda: Implications for Food Security - Wambede, Nabalegwa Muhamud; Sharon, Alonyo; JoyFred, Asaba; Mulabbi, Andrew; Robert, Tweheyo (Department of Agronomy and Horticulture, IPB University, 2025)
This study examined the relationship between climate variability adaptation strategies and household food security. Specifically, it investigated the adaptation practices employed by farmers and assessed their impact on food availability by comparing food security outcomes between adapting and non-adapting households. Data were collected from 375 randomly selected households in Agoro and Madi Opei sub-counties, known for their transitional climatic conditions. Employing questionnaires, field observations, and key informant interviews, the study found early planting (38.2%), new crop varieties (25.4%), drought-resistant crops (21.6%), and small-scale irrigation (7.8%) to be the primary on-farm adaptations, while motorcycling (50%), retail (25%), and construction-related activities (10%) dominated off-farm strategies. In the surveyed households, 1.2% experienced inadequate food availability, 95.7% exhibited moderate food security, and 3.1% demonstrated adequate food security. The study revealed a positive correlation between adaptation practices and food security, suggesting that various adaptation strategies can enhance household resilience to climate variability.